Occupational stress and psychosocial risk among journalists - Anna Najder; Dorota Merecz-Kot (Nofer Institute of Occupational Medicine, 2014)
Background: Traumatic stress symptoms in journalists are well known but chronic occupational stress in this professional group is still to be elucidated. This study aimed at answering the following questions: (1) which of psychosocial risks (PRs) are most frequently reported as stressogenic in journalists, (2) are there any differences in exposure to PRs and their stressfulness between journalists and other professional groups, (3) what relationships occur between PR categories of stressfulness and their consequences for employees' functioning in the job, and (4) what is the risk of negative consequences of stress (health deterioration and worse job performance). Materials and Methods: The Psychosocial Risk Scale was used to investigate general and specific PRs at work and the stressfulness of particular PRs. A group of 211 journalists working in Polish newspapers, radio and TV editorial offices participated in the study. Results: The journalists experienced occupational stress at an average level, but at significantly lower than other professional groups. The study revealed the risk of health self-assessment deterioration, depending on specific risks (OR = 1.849, 95% CI: 1.068-3.203), risk of work organization dissatisfaction due to the impact of stress arising from the contextual job characteristics (OR = 1.942, 95% CI: 1.125-3.352) and dissatisfaction with relationships with coworkers due to the stressfulness of pathologies occurring in the workplace (OR = 2.012, 95% CI: 1.184-3.419). Conclusions: The study results evidence that occupational stress experienced by journalists determine the risk of health self-assessment, satisfaction with work organization and interpersonal relationships. The presented outcomes indicate that regardless of the experienced stress level it is necessary to assess the psychosocial risk because even an average level of stressfulness could be associated with the risk of adverse consequences for employees in terms of their job performance. Med Pr 2014;65(1):85-97